Vegetation, fire and soil feedbacks of dynamic boundaries between rainforest, savanna and grassland. (23rd August 2016) - MacDermott, Harry J.; Fensham, Roderick J.; Hua, Quan; Bowman, David M. J. S.
Abstract: At fine spatial scales, savanna‐rainforest‐grassland boundary dynamics are thought to be mediated by the interplay between fire, vegetation and soil feedbacks. These processes were investigated by quantifying tree species composition, the light environment, quantities and flammability of fuels, bark thickness, and soil conditions across stable and dynamic rainforest boundaries that adjoin grassland and eucalypt savanna in the highlands of the Bunya Mountains, southeast Queensland, Australia. The size class distribution of savanna and rainforest stems was indicative of the encroachment of rainforest species into savanna and grassland. Increasing dominance of rainforest trees corresponds to an increase in woody canopy cover, the dominance of litter fuels (woody debris and leaf), and decline in grass occurrence. There is marked difference in litter and grass fuel flammability and this result is largely an influence of strongly dissimilar fuel bulk densities. Relative bark thickness, a measure of stem fire resistance, was found to be generally greater in savanna species when compared to that of rainforest species, with notable exceptions being the conifers Araucaria bidwillii and Araucaria cunninghamii . A transect study of soil nutrients across one dynamic rainforest – grassland boundary indicated the mass of carbon and nitrogen, but not phosphorus, increased across the successional gradient. Soil carbon turnover time is shortest in stable rainforest, intermediate in dynamic rainforest and longest in grassland highlighting nutrient cycling differentiation. We conclude that the general absence of fire in the Bunya Mountains, due to a divergence from traditional Aboriginal burning practices, has allowed for the encroachment of fire‐sensitive rainforest species into the flammable biomes of this landscape. Rainforest invasion is likely to have reduced fire risk via changes to fuel composition and microclimatic conditions, and this feedback will be reinforced by altered nutrient cycling. The mechanics of the feedbacks here identified are discussed in terms of landscape change theory.